Variação sazonal dos perfis proteico e energético de caprinos no semiárido - Vale, Rodolfo Gurgel (Universidade Federal Rural do Semi-Árido, 2015)
Creation of goats has an important socio-economic role in the Northeast, concentrating more than 90% of the national herd. This limited activity in this region is for the seasonal rainy period short and low rainfall intensity; restricting the forage supply along the year and favoring the appearance of deficiency and metabolic diseases. This fact stresses the need for seasonality effects of study on energy and protein profile goats extensively created any semiarid Rio Grande do Norte. Were used 20 goats without defined standard racial, male, neutered, healthy, kept two properties, separated into two groups of 10 animals, during 12 months. The blood was collected monthly paragraph rating protein (total protein, albumin and urea) and energy (betahydroxybutyrate, fatty acids esterified not, glucose and cholesterol). Following the reference values literature consulted none of the above variables showed superior values. Among variables such as protein albumin, a protein total, urea values critics had no definite dry period. In the energy assessment, during the rainy season, glucose and cholesterol values showed minor, while the beta-hydroxybutyrate and esterified fatty acids presented no more values indicating the energy deficit especially in this season of the year. That way we can infer the need for energy supplementation no rainy period and protein do not definite dry period, paragraph goats extensive created a non semiarid Northeast
Seasonal variation of the protein profiles and energy goats in semiarid
Keywords: Goats; Supplementation; Supplementation protein; Metabolism - goats; Semiarid region - Northeast Brazil; Caprinos; Suplementação energértica; Suplementação protéica; Metabolismo - caprinos; Semiárido - nordeste brasileiro; CIENCIAS AGRARIAS::MEDICINA VETERINARIA